Causes of Domestic Violence from the Point of View of Neobehaviorism - Ziyavutdinova.H.Sh. (Genius Journals, 2022)
This article discusses the causes of domestic violence in Uzbek families. Domestic violence is any physical, sexual or psychological abuse by other family members that endangers the psyche or health of family members. Based on the neobehaviorist approach, violent behavior in the family is considered to be acquired in the process of socialization as a result of observing examples of such behavior in the parental family.
Keywords: Domestic violence; violence against women; mental discrimination; physical violence